Summary scores captured changes in subjects' QoL as measured by the multiple scales of the EORTC QLQ-C30 - Phillips, Rachel; Gandhi, Mihir; Cheung, Yin Bun; Findlay, Michael P.; Win, Khin Maung; Hai, Hoang Hoa; Yang, Jin Mo; Lobo, Rolley Rey; Soo, Khee Chee; Chow, Pierce K.H. (Journal of clinical epidemiology, 2015)
To examine the performance of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) global health status/quality of life (QoL) scale and two summary scores to detect changes in the QoL profile over time, according to changes in the individual scales. Data came from 167 clinical trial patients with unresectable (advanced) hepatocellular carcinoma. The global health status/QoL scale of the questionnaire contained two items: overall health and overall QoL. Nordin and Hinz proposed summary scores for the questionnaire. A mixed-effect model was fitted to estimate trends in scores over time. Predominantly the individual scale scores declined over time; however, the global health status/QoL score was stable [rate of change = −0.3 per month; 95% confidence interval (CI): −1.2, 0.6]. Nordin's summary score, which gave equal weight to the 15 questionnaire scales, and Hinz's summary score, which gave equal weight to the 30 questionnaire items, showed a statistically significant decline over time, 3.4 (95% CI: −4.5, −2.4) and 4.2 (95% CI: −5.3, −3.0) points per month, respectively. In contrast to the global health status/QoL scale, the summary scores proposed by Nordin and Hinz detected changes in subjects’ QoL profile described by the EORTC QLQ-C30 individual scales.